Profile and outcome of treatment in non-small cell lung cancer with brain metastasis - Rehman, Uzma; Khan, Nazir Ahmed; Nasreen, Shahida; Gadda, Irfan Rasool (International Journal of Research in Medical Sciences, 2024)
Background: Brain metastasis is a common problem in patients with NSCLC. This study was done to study the risk factors associated with the development of brain metastasis and assess treatment response in NSCLC to improve patient survival. Methods: This was a retro-prospective study in which 126 patients with non-small cell lung carcinoma with brain metastasis were taken for the study. Results: The mean age in study group was 56.1±12.72 years. Adenocarcinoma was found in 57.1% and squamous cell carcinoma in 41.3% patients. 65.9% patients received chemotherapy for primary disease followed by targeted therapy in 34 (27.0%) patients. 53.9% patients received WBRT after diagnosis of brain metastasis and 23% WBRT and systemic chemotherapy while as14.3% received WBRT and targeted therapy and 2.4% received WBRT, systemic chemotherapy and targeted therapy, 1.6% patients received systemic chemotherapy, WBRT and local RT to the primary site and 0.8% each was treated with gamma knife therapy; surgery, WBRT and targeted therapy; SRS and WBRT. Median overall survival of patients with brain metastasis who received WBRT was 2.5 months and patients who received WBRT and systemic chemotherapy was 9.0 months while patients with brain metastasis who received WBRT and targeted therapy was 14.3 months. Conclusions: The median overall survival as per treatment received after diagnosis of brain metastasis was higher in patients who received WBRT and targeted therapy as compared to patients who received WBRT and systemic chemotherapy and patients who received WBRT only.